RECULTIVATED SOIL HETEROGENEITY: ECOLOGICAL ASPECT - Zadorozhnaya, Galina; Andrusevych, Kateryna (My University, 2018)
Extracting minerals by the open method leads to the removal of the rocks to the surface which significantly disturbs natural processes in biogeocoenoses. After remediation activities anthropogenic biogeocoenoses are formed. In this biogeocoenosis on the rocks man-made soils are formed under the influence of environmental factors. Such man-made soils are called technozems.
Keywords: Soil Heterogeneity; Soil Penetration Resistance; Recultivation; Phytoindication; Geostatistics